2010
DOI: 10.1063/1.3258029
|View full text |Cite
|
Sign up to set email alerts
|

Boron ion source based on planar magnetron discharge in self-sputtering mode

Abstract: An ion source based on a planar magnetron sputtering device with thermally isolated target has been designed and demonstrated. For a boron sputtering target, high target temperature is required because boron has low electrical conductivity at room temperature, increasing with temperature. The target is well-insulated thermally and can be heated by an initial low-current, high-voltage discharge mode. A discharge power of 16 W was adequate to attain the required surface temperature (400 degrees C), followed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…The boron rich compound B 4 C has been selected previously over boron because of its higher electrical conductivity [9] which simplifies deposition with commonly used DC magnetron sputtering techniques. Boron, being a semi-conductor at room temperature, is usually deposited by RF magnetron sputtering, but DC magnetron sputtering sources can be employed for boron when the target is heated above 400°C [10], where the conductivity improves sufficiently.…”
Section: Introductionmentioning
confidence: 99%
“…The boron rich compound B 4 C has been selected previously over boron because of its higher electrical conductivity [9] which simplifies deposition with commonly used DC magnetron sputtering techniques. Boron, being a semi-conductor at room temperature, is usually deposited by RF magnetron sputtering, but DC magnetron sputtering sources can be employed for boron when the target is heated above 400°C [10], where the conductivity improves sufficiently.…”
Section: Introductionmentioning
confidence: 99%
“…LaB 6 was primarily selected for its very large fraction of boron, an element of many uses. Although it has been demonstrated that pure boron can be used in HiPIMS discharges, 15 working with pure boron targets is difficult. First, the electrical conductivity at room temperature is insufficient for HiPIMS unless a high target temperature of 600°C or higher is used.…”
mentioning
confidence: 99%
“…The described equipment will be used to obtain pure boron coatings, promising for use in modern electronic devices and extreme ultra-violet optics, and boron nitride coatings with high hardness, which are in demand for surface hardening tasks in the industry. The considered methods for obtaining pure boron coatings using magnetron discharge [20] and forevacuum electron source [21] are original and first implemented by the authors of the article. The analog of the first method can be considered a highfrequency magnetron discharge with a dielectric target [19].…”
Section: Discussionmentioning
confidence: 99%
“…This article discusses the equipment for the implementation of two plasma methods developed by us for depositing thin films of pure boron to the surface. The first is the use of a magnetron with a heated target made of pure crystalline boron, in which its specific resistance decreases to a value at which the magnetron discharge can function normally [20]. The second is the use of a fore-vacuum source of electrons for heating a pure boron target and its evaporation.…”
Section: Introductionmentioning
confidence: 99%